Prior Vancomycin Use Is a Risk Factor for Reduced Vancomycin Susceptibility in Methicillin-Susceptible but Not Methicillin-Resistant Staphylococcus aureus Bacteremia - Mascitti, Kara B. (2011)
OBJECTIVE: Staphylococcus aureus is a cause of community- and healthcare-acquired infections and is associated with substantial morbidity, mortality, and costs. Vancomycin minimum inhibitory concentrations (MICs) among S. aureus have increased, and reduced vancomycin susceptibility (RVS) may be associated with treatment failure. We aimed to identify clinical risk factors for RVS in S. aureus bacteremia. DESIGN: Case-control. SETTING: Academic tertiary care medical center and affiliated urban community hospital. PATIENTS: Cases were patients with RVS S. aureus isolates (defined as vancomycin E-test MIC >1.0 μg/mL). Controls were patients with non-RVS S. aureus isolates. RESULTS: Of 392 subjects, 134 (34.2%) had RVS. Fifty-eight of 202 patients (28.7%) with methicillin-susceptible S. aureus (MSSA) isolates had RVS, and 76 of 190 patients (40.0%) with methicillin-resistant S. aureus (MRSA) isolates had RVS (P =.02). In unadjusted analyses, prior vancomycin use was associated with RVS (odds ratio [OR], 2.08; 95% confidence interval [CI], 1.00–4.32; P =.046). In stratified analyses, there was significant effect modification by methicillin susceptibility on the association between vancomycin use and RVS (P = .04). In multivariable analyses, after hospital of admission and prior levofloxacin use were controlled for, the association between vancomycin use and RVS was significant for patients with MSSA infection (adjusted OR, 4.02; 95% CI, 1.11–14.50) but not MRSA infection (adjusted OR, 0.87; 95% CI, 0.36–2.13). CONCLUSIONS: A substantial proportion of patients with S. aureus bacteremia had RVS. The association between prior vancomycin use and RVS was significant for patients with MSSA infection but not MRSA infection, suggesting a complex relationship between the clinical and molecular epidemiology of RVS in S. aureus.